A study on some small-celled Halamphora (Bacillariophyta) taxa from the Black Sea and the Adriatic Sea, with the description of eleven new species - Zidarova, Ralitsa; Pottiez, Margaux; de Haan, Myriam; Ivanov, Plamen; Kanjer, Lucija; Bosak, Sunčica (Phytotaxa, 2025)
In this work we present the observations on 19 Halamphora taxa found in a small set of samples originating from the summer biofilm on artificial substrates (plexiglass) in the western Black Sea or from macroalgae during winter in the Adriatic Sea. One taxon was also found on the carapace of a loggerhead sea turtle during summer in the Adriatic Sea. Most taxa had small valve dimensions, usually reaching not more than 20 µm in length and 2–3 µm in width, with only a few exceptions. Following extensive light (LM) and scanning electron microscope (SEM) observations, two taxa were identified based on the literature: H. bistriata was observed in the summer biofilm on artificial substrates in the Black Sea and on the carapace of a loggerhead sea turtle in the Adriatic Sea, whereas H. tenuicostata was detected as an epiphyte on macroalgae in the Adriatic Sea during winter. Eleven other taxa, of which 6 taxa from the Black Sea and 5 taxa from the Adriatic Sea, were described as new species, comparing their morphology to that of already known taxa. The remaining six unidentified taxa were observed sporadically. They are only illustrated and shortly discussed, without a formal description. The study demonstrates the remarkable and yet unexplored diversity of coastal marine benthic Halamphora species.